Please see attached file...
Follow Math Help Forum on Facebook and Google+
Originally Posted by Alienis Back Please see attached file... You went wrong in the 5th step, The correct thing to do was $\displaystyle \frac{5 + x^2}{x^2} = \frac{6}{x}$. You have written $\displaystyle \frac{5x^2}{x^2} = \frac{6}{x}$. Now continue
Originally Posted by Alienis Back Please see attached file... Hi Alienis Back I would approach it this way: $\displaystyle 1+5x^{-2}=6x^{-1}$ $\displaystyle 1+\frac{5}{x^2}=\frac{6}{x}$ Now multiply each term by $\displaystyle x^2$ $\displaystyle x^2+5=6x$ $\displaystyle x^2-6x+5=0$ Factor and solve.
View Tag Cloud